2000
DOI: 10.1139/t99-085
|View full text |Cite
|
Sign up to set email alerts
|

Tire-reinforced earthfill. Part 2: Pull-out behaviour and reinforced slope design

Abstract: The disposal of scrap tires has become a major environmental concern. The reuse of scrap tires in the reinforcement of earth structures can provide an attractive solution in reducing the number of used tires disposed in overcrowded landfills. This paper, the second in a series of three papers, discusses the behaviour of slopes reinforced with scrap tires and proposes design recommendations. A mat-reinforced slope can either fail by pull-out of the reinforcement or due to rupture of the attachment tying the tir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…7 together with the results of tests reported by O'Shaughnessy and Garga (2000a) and Gerscovich et al (2001). All normalized pullout resistance behavior can be represented by a respective single curve, and the values converge to a constant value as the number of tires increases.…”
Section: Ultimate Pullout Resistancementioning
confidence: 58%
See 2 more Smart Citations
“…7 together with the results of tests reported by O'Shaughnessy and Garga (2000a) and Gerscovich et al (2001). All normalized pullout resistance behavior can be represented by a respective single curve, and the values converge to a constant value as the number of tires increases.…”
Section: Ultimate Pullout Resistancementioning
confidence: 58%
“…The test setups of O'Shaughnessy and Garga (2000a) and Gerscovich et al (2001) were similar to each other. O'Shaughnessy and Garga (2000a) and Gerscovich et al (2001) compacted mechanically the embankment and the inside of the tires with equipment. However, the surcharge and slope in front of the first row of tire mats was kept in a loose state to reduce the passive resistance of the soil.…”
Section: Ultimate Pullout Resistancementioning
confidence: 89%
See 1 more Smart Citation
“…Some studies indicated that tyre chip-soil mixtures exhibit a significant initial plastic compression under loading and are highly compressible at normal low pressures [2,4]. Some other researches indicated that large strain ranged from 19.6% to 44 6% required to fully mobilizing the ultimate pull-out capacity [12]. To date there is no report on field application of fibreglass for soil improvement, soil erosion and slope stability.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many experimental and field studies have been performed on the environments and fluids which are placed next to these materials. The obtained results show that no harmful effect is relevant and the only environmental limitation in the use of crumb rubber is related to their self-ignition potential [1][2][3][4]. In1998, the ASTM regulation provided the D6270 instruction to decrease this potential.…”
mentioning
confidence: 99%